N-glycans from human milk glycoproteins are selectively released by an infant gut symbiont in vivo. (October 2019) - Karav, Sercan; Casaburi, Giorgio; Arslan, Aysenur; Kaplan, Merve; Sucu, Berfin; Frese, Steven
Graphical abstract: Highlights: EndoBI-1, an endo-β-N-acetylglucosaminidase, is an enzyme unique to B. infantis. This enzyme cleaves the chitobiose core of N- glycans bound to glycoproteins. EndoBI-1 is active in vivo and releases N -glycan from human milk glycoproteins. These N- glycans are selectively utilized by B. infantis. Abstract: Complex, indigestible free oligosaccharides as well as conjugated glycans are found in milk that shape the gut microbiome of infants. The activity of an endo-β- N -acetylglucosaminidase from B. longum subsp. infantis ( B. infantis ) is known to release N -glycans from native milk glycoproteins under physiological conditions. We investigated whether this enzyme is active in vivo in breastfed infants fed B. infantis EVC001. Using mass spectrometry, we found 19 N -glycans related to human milk glycoproteins increased in abundance, similar to previous work using bovine milk glycoproteins, and these 19 N -glycans matched unique specificities of this enzyme. Twenty N -glycans were unique to infants fed B. infantis EVC001. Bifidobacteriaceae were correlated with these glycans, confirming the relationship between B. infantis and released N -glycans. This suggests that this enzyme is active in vivo and releases N -glycans from milk glycoproteins, and may play a role in B. infantis EVC001 colonization of the gut microbiome.